2005
DOI: 10.1542/peds.2005-0969
|View full text |Cite
|
Sign up to set email alerts
|

Early Presentation With Angioedema and Urticaria in Cross-reactive Hypersensitivity to Nonsteroidal Antiinflammatory Drugs Among Young, Asian, Atopic Children

Abstract: ABSTRACT. Objective. Nonsteroidal antiinflammatory drugs (NSAIDs), mainly ibuprofen, are used extensively among children as analgesic and antipyretic agents. Our initial survey in the Kendang Kerbau Children's Hospital in Singapore showed NSAIDs to be the second most common adverse drug reaction-causing medications among children of Asian descent. We attempted to characterize the clinical and epidemiologic profile of NSAID reactions in this group of patients.Methods. A retrospective case series from a hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 32 publications
7
65
3
1
Order By: Relevance
“…Our previously published protocol [10] is now further modified according to the accumulated experience in small children and the need to tailor challenges to a wide variation in weight and maturity. The published adult protocol for urticaria and angioedema reactions in normal individuals (patients without chronic urticaria) [2] calls for a small initial dose with half-hourly doubling (similar to oral provocation protocols with antibiotics).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previously published protocol [10] is now further modified according to the accumulated experience in small children and the need to tailor challenges to a wide variation in weight and maturity. The published adult protocol for urticaria and angioedema reactions in normal individuals (patients without chronic urticaria) [2] calls for a small initial dose with half-hourly doubling (similar to oral provocation protocols with antibiotics).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that an early onset of symptomatic hypersensitivity is also a hallmark of increased sensitivity, making paracetamol, with its diminished COX inhibitor capacity but wider exposure, a major eliciting medication for these children. As a group, Asian children, especially atopic children, seem to be at increased risk for hypersensitivity reactions to COX inhibitors [10, 18], with early presenters most likely representing the more severe spectrum of disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asthma and hypersensitivity reactions have long been a cause for concern in children and the cross-reactions of ibuprofen with aspirin-sensitive asthma have been highlighted by several authors (Body and Potier 2004;Kidon et al 2005;Mascia et al 2005;Debley et al 2005;Kanabar 2007;Ponvert and Scheinmann 2007). Two large scale studies in febrile asthmatic children (McIntyre and Hull 1996;Lesko et al 2002) found that ibuprofen far from being associated with increased risk of asthma compared with paracetamol actually showed a slightly reduced risk.…”
Section: Asthma and Hypersensitivity Reactions In Childrenmentioning
confidence: 99%